FATAL HOMICIDAL FIREARM INJURIES ON THE HEAD (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
The head is a common target for homicidal attacks. This has been well proved by the use of protective helmets by warriors  through ages. Though in the past, homicidal injuries in the head were mostly by blunt or sharp weapons the situation has changed  very much these days where firearms are used commonly. A number of factors make the head the target of choice in homicidal  firearm attacks. With the use of fatal weapons like firearms death is almost certain. It also causes very early death i.e. time interval  between injury and death is very less and in rare cases where the victims survive they are unable to give any statement due to  loss of consciousness.
Keywords: firearms; victims